The Role of Sukuk Financing for Sustainable Development of Smallholder Farmers - Sugiharto Soeleman; Setyani Dwi Lestari (Australasian Accounting, Business and Finance Journal, 2015)
The greatest advance made by mankind was probably the agricultural revolution that has been developed into agricultural development along with population growth in the forms of agricultural expansion and agricultural intensification. The global land grab driven by the acquisition of land has caused radical changes in the use and ownership of land and has important implications for equitable and sustainable development in which local people have been moved to marginal locations. To ensure that the agricultural activities are sustained, a balance of three concepts of people, planet, and profit (3P) are critical to achieve long term social, environmental, and economic issues. One of recently popular instruments to fairly treat the people is an equity based Sukuk in which profit will be shared based on pre-agreed ratio between the investors and the people involved. In term of conservation of planet, strategy in selecting the agricultural commodities and the timing of harvesting are critical. An investment decision-making process by using agricultural appraisal process is established to ensure that the agricultural activities are financially profitable.
Keywords: agricultural appraisal; agricultural development; investment decision; smallholder farmers; sukuk financing; sustainable development